PENGARUH INFLUENCER MARKETING DAN CONTENT MARKETING TERHADAP MINAT BELI KONSUMEN PADA PRODUK PROPERTY DI PERUMAHAN PANORAMA SEPATAN 1 KABUPATEN TANGERANG - Sri Utami Faridah; Erlita Kurniawaty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
. The purpose of this study is to determine the effect of influencer marketing and content marketing on consumer purchasing interest both partially and simultaneously. This study uses a quantitative method. The population in this study was 592 buyers in 2023-2024. Sampling was taken using random sampling techniques or probability sampling with the Slovin theory method so that a sample of 86 respondents was obtained. The sample data collection techniques used were observation and questionnaires. Data analysis techniques used were descriptive analysis and quantitative analysis, multiple linear regression techniques, correlation coefficient analysis, determination coefficient, and hypothesis. The results of the study obtained partially (t-test) concluded that influencer marketing had a positive and significant effect on consumer purchasing interest with a calculated t value > t table or (1.994 > 1.988) and a ρ value < Sig. 0.050 or (0.000 < 0.050). Content marketing has a positive and significant effect on consumer purchase intention, with a calculated t-value > t-table (2.871 > 1.988) and a ρ value < Sig. 0.050 (0.000 < 0.050). Simultaneously (F-test), the influencer marketing and content marketing variables have a positive and significant effect on consumer purchase intention, with a calculated F-value > F-table (11.260 > 3.106) and a ρ value < Sig. 0.050 (0.000 < 0.050). Keywords: Influencer Marketing, Content Marketing, and Consumer Purchase Intention